2011
DOI: 10.1016/j.yjmcc.2011.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor involvement in myocardial remodeling following infarction

Abstract: Aims Cardiac remodeling occurs in the infarcted heart (MI). The underlying regulatory mechanisms are under investigation. Platelet-derived growth factor (PDGF) is a family of growth factors that stimulates cell growth, differentiation and migration. Herein, we sought to determine whether PDGF is involved in cardiac repair/remodeling following MI. Methods and Results The temporal and spatial expression of PDGF isoforms (A, B, C and D) and PDGF receptor (PDGFR)-α and β as well as cell types expressing PDGF wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 35 publications
0
73
1
1
Order By: Relevance
“…The cardiac-restricted overexpression of either PDGF-C or PDGF-D caused cardiac fibrosis and dilated cardiomyopathy in mice [12,13]. PDGF also plays an important role in cardiac fibrosis after myocardial infarction [14]. Recently, some researches indicated that PDGF may represent a novel mediator of AF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cardiac-restricted overexpression of either PDGF-C or PDGF-D caused cardiac fibrosis and dilated cardiomyopathy in mice [12,13]. PDGF also plays an important role in cardiac fibrosis after myocardial infarction [14]. Recently, some researches indicated that PDGF may represent a novel mediator of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac-restricted overexpression of PDGF-C/D caused cardiac fibrosis and dilated cardiomyopathy in mice [12,13]. PDGF-A/D and PDGF receptor-α/β (PDGFR-α/β) increased in the infarcted heart, which contributed to cardiac fibrosis after myocardial infarction [14]. Cardiac mast cells caused atrial fibrosis, which enhanced AF susceptibility through PDGF-A signaling in pressure-overloaded mouse hearts [15].…”
Section: Introductionmentioning
confidence: 99%
“…84,85 After myocardial infarction, PDGF-A and D are significantly increased in endothelial cells, macrophages, and myofibroblasts. 86 Enhanced PDGF-A, PDGF-D, and PDGF receptors are coincident with angiogenesis and inflammatory and fibrogenic responses in the infarcted myocardium, suggesting their regulation on cardiac repair. 86 Transgenic mice overexpressing the active core domain of PDGF-D in the heart displayed enhanced proliferation of both cardiac interstitial fibroblasts and arterial vascular smooth muscle cells resulting in cardiac fibrosis followed by dilated cardiomyopathy and, subsequently, cardiac failure.…”
Section: Platelet-derived Growth Factormentioning
confidence: 99%
“…86 Enhanced PDGF-A, PDGF-D, and PDGF receptors are coincident with angiogenesis and inflammatory and fibrogenic responses in the infarcted myocardium, suggesting their regulation on cardiac repair. 86 Transgenic mice overexpressing the active core domain of PDGF-D in the heart displayed enhanced proliferation of both cardiac interstitial fibroblasts and arterial vascular smooth muscle cells resulting in cardiac fibrosis followed by dilated cardiomyopathy and, subsequently, cardiac failure. 87 In vitro, PDGF-D significantly enhanced TGF-β1 synthesis, which was eliminated by TGF-β blockade with small interfering RNA; moreover, the stimulatory role of PDGF-D on fibroblast proliferation and collagen synthesis was abolished by TGF-β blockade.…”
Section: Platelet-derived Growth Factormentioning
confidence: 99%
“…PDGF has also been identified as a significant contributor to angiogenesis and cardiac remodeling following MI [56][57][58] . Notably, both VEGF and PDGF have demonstrated some adverse effects, particularly when given in high intravenous doses.…”
Section: Cytokines Role "Vegf and Pdgf"mentioning
confidence: 99%